Effects of different levels of modified palygorskite supplementation on the growth performance, immunity, oxidative status and intestinal integrity and barrier function of broilers. Issue 6 (16th August 2018) - Su, Yue; Chen, Yueping; Chen, Lingjie; Xu, Qiao; Kang, Yuru; Wang, Wenbo; Wang, Aiqin; Wen, Chao; Zhou, Yanmin
Abstract: This experiment was designed to investigate effects of different levels of modified palygorskite (MPal) supplementation on growth performance, immunity, oxidative status and intestinal integrity and barrier function of broilers. A total of 320 1‐day‐old Arbor Acres broilers were randomly assigned into 5 dietary treatments and fed a basal diet supplemented with 0, 0.25, 0.5, 1 and 2 g/kg MPal, respectively, for a 42‐day feeding trial. Treatments quadratically reduced feed/gain ratio (F:G) during 1–21 days and linearly decreased average daily feed intake and F:G during 22–42 days, and linearly and quadratically decreased average daily feed intake and F:G during overall period ( p  <   0.05, 0.50 g/kg treatment showed the lowest F:G). MPal supplementation increased the contents of 21‐day jejunal secretory immunoglobulin A (SIgA) quadratically, and 21‐day jejunal immunoglobulin G (IgG), immunoglobulin M (IgM) and 42‐day jejunal total superoxide dismutase (T‐SOD) activity linearly and quadratically (0.50 g/kg treatment showed the highest immunoglobulin concentration), whereas linearly reduced 21‐day ileal SIgA level and 42‐day jejunal malondialdehyde (MDA) accumulation and serum diamine oxidase activity, and quadratically decreased 21‐day ileal MDA level ( p  <   0.05). The 42‐day jejunal SIgA, IgG and IgM concentrations, and T‐SOD activity in jejunum at 21 days and ileum at both 21 days and 42 days were quadratically increased with MPal administration ( p  <   0.05, 0.50 g/kg treatment showed the highest T‐SOD activity). The mucin 2 mRNA abundances in 42‐day jejunum and 21‐day ileum were quadratically increased with MPal supplementation ( p  <   0.05). Treatments linearly increased 42‐day ileal zonula occludens‐1, claudin‐3 and jejunal claudin‐3 mRNA level, whereas linearly and quadratically increased ileal claudin‐2 mRNA level ( p  <   0.05). In conclusion, MPal supplementation exhibited beneficial effects on growth performance, intestinal immunity, antioxidant capacity and intestinal integrity and barrier function of broiler with its optimum dosage being 0.5 g/kg.